Longitudinal quantitative assessment of coronary atherosclerosis related to normal systolic blood pressure maintenance in the absence of established cardiovascular disease - Won, Ki Bum (2022)
Funding Information: The project was conducted within the framework of a "Multidisciplinary Survey and Monitoring of the Gareja Rock Cut Complex, the Monument of National Value" funded by the National Agency for Cultural Heritage Preservation of Georgia and managed by the Ilia State University, Georgia, together with the Italian Institute for Environmental Protection and Research, Italy, and the support of the University of Milano-Bicocca, Italy. Data used in this work was jointly acquired and, accordingly, belongs to all three institutions.